ANALISA SANKSI PIDANA TERHADAP PELAKU PENCURIAN DALAM KEADAAN MEMBERATKAN DI WILAYAH HUKUM PENGADILAN NEGERI SINTANG STUDI KASUS (PN SINTANG Nomor 237/Pid.B/2017/PN Stg Tahun 2017) - Kartika Agus Salim (Universitas Kapuas Sintang, 2020)
The theft mode of the four defendants is by jointly harvesting oil palm fruit belonging to PT. SDK 4 Bukit Benua Block 13QQ slices B and C located in Penjernang Hulu Village, Sungai Tebelian District, Sintang Regency. The harvested palm oil is then transported to the side of the road and arranged with a total of 102 (one hundred two) pieces of fresh palm oil bunches of about 2 (two) tons to be sold. It was not yet possible to be transported for sale that TJ, a harvest inspector and a West Kalimantan Regional Police Mobile Brigade, who were conducting routine patrols in the PT. SDK 4 Bukit Benua, then at 12:30 a.m. Witness witnessed diareal Block 13 QQ sliced Bdan C found there were 6 (six) people who were illegally harvesting to steal the area’s palm oil and Brimob succeeded in securing evidence of palm fruit, egrek and one unit the defendant’s motorcycle, the defendant ran away.Keywords: Analysis, Sanctions, Theft.